2010
DOI: 10.1111/j.1440-1827.2009.02510.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of podoplanin in human bone and bone tumors: New marker of osteogenic and chondrogenic bone tumors

Abstract: Podoplanin is known as a lymphatic marker because its expression is detected in lymphatic but not vascular endothelium. Podoplanin is also expressed in several normal tissues including osteocytes or osteoblasts. A systematic examination of the podoplanin expression was conducted in normal skeletal tissues and some bone tumor cell lines, and the diagnostic value determined in primary bone tumors. Podoplanin mRNA was expressed at a high level in bone marrow tissue and cartilage, and was upregulated with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
55
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 42 publications
0
55
0
Order By: Relevance
“…28 That none of the small cell mesotheliomas in this study were found to express CD99, a marker that is almost invariably strongly expressed in Ewings sarcoma/PNETs, indicates that immunostaining for this marker, when used in conjunction with some positive mesothelioma markers, such as WT1, podoplanin and mesothelin, which are negative in Ewings sarcoma/ PNETs, [29][30][31][32][33] can help in distinguishing between these two malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…28 That none of the small cell mesotheliomas in this study were found to express CD99, a marker that is almost invariably strongly expressed in Ewings sarcoma/PNETs, indicates that immunostaining for this marker, when used in conjunction with some positive mesothelioma markers, such as WT1, podoplanin and mesothelin, which are negative in Ewings sarcoma/ PNETs, [29][30][31][32][33] can help in distinguishing between these two malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…47 In addition, immature human OS cell lines such as MG-63, but not more mature human OS cells like Saos-2, and two cases of small cell osteosarcoma, which is a rare subtype of OS, 34 are reported to show the same membranous immunohistochemical staining. 7 Moreover, whereas c-Fos transgenic OS in vivo rarely showed strong specific membranous podoplanin antibody labeling, c-Fos transgenic OS-derived cell lines and their resulting tumor xenografts showed an intensive membranous podoplanin immunostaining. This further supports our notion that the normally tight control of podoplanin expression in normal bone appears to be lost in immature tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…7 OS are known to express aberrantly a wide range of osteoblast differentiation markers, including transcription factors, serum enzymes such as alkaline phosphatase, noncollagenous bone proteins, and cell surface antigens. 48 As tumor cells in OS are generally regarded as being immature, previous studies have focused typically on analyzing marker genes of early osteoblast differentiation, rather than late stage and fully differentiated osteoblast phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 However, it has recently attracted attention in areas of cancer research because various kinds of tumor cells have been shown to express PDPN. [5][6][7][8][9]34 In oral cancer, PDPN expression has been related to poor clinical outcomes, including lymph node metastasis or to malignant transformation of precancerous lesions, although its molecular function has not been well understood. [10][11][12][13]35 To elucidate its function, we carried out comparative immunohistochemical studies between PDPN and the other molecules, which are related to cell proliferation or differentiation in oral mucosal malignancies 13 or odontogenic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, PDPN expression has been also confirmed in various types of tumor cells, including squamous cell carcinoma (SCC). [5][6][7][8][9][10][11] In the field of oral cancer, PDPN has also been regarded as a biomarker in predicting the risk of cancer development and poor clinical outcome. [10][11][12] We have also shown the PDPN expression profiles to be a useful immunohistochemical aid in the differential diagnosis of oral carcinoma in situ (CIS) from epithelial dysplasia because PDPN positive ( þ ) cells are distributed more widely in CIS than in epithelial dysplasia, overlapping with Ki-67 þ -proliferating cell zones.…”
mentioning
confidence: 99%